Evaluation of antioxidant, anti-inflammatory, and anti-hyperglycemic effects of Wattakaka volubilis Linn. f. (January 2022) - Maya, M.R.; Rameshkumar, K.; Veeramanikandan, V.; T., Boobalan; Kumar, M.; Eyini, M.; Arun, A.; Pugazhendhi, Arivalagan; Balaji, P.
Graphical abstract: Highlights: First report of Wattakaka volubilis Linn. F. on antihyperglycemic effect. in vitro antioxidants ability of W. volubilis have been established. The chromatography method was performed to determine the class of compounds. Anti-hyperglycemic effect of HWE and AE were assessed in alloxan induced diabetic mice. Abstract: The phytochemicals, antioxidants, antiinflammatory and the anti-hyperglycemic properties of Wattakaka volubilis Linn. F were determined. The Hot Water Extract (HWE) and Acetone Extracts (AE) of W. volubilis leaves were tested for a variety of phytochemicals. The preliminary analysis revealed the presence of a large number of phytochemicals. The DPPH assay was used to measure the free radical scavenging activity of both HWE and AE. The HWE had the highest DPPH scavenging rate (87.72 %t), followed by the AE (33.33 %). At 500 g/mL concentration, the anti-inflammatory activity of HWE, AE, and Diclofenac (standard drug) was 54.27 %, 49.88 %, and 83.33 %, respectively. Orally administered alloxan (75 mg/kg body weight) resulted in a significant (p 0.05) decrease in blood glucose levels in diabetic mice with HWE and AE at 200 mg/kg b.wt for 4 weeks. Aside from all hypoglycemic parameters, the histopathology of the pancreas was also controlled, indicating that HWE exerted greater anti-diabetic activity than AE. Furthermore, HWE supported a significant inhibition of -amylase enzyme activity, with the highest action of 99.23 % reticence at 1000 g/mL. The findings indicate that HWE has a potential antidiabetic effect; thus, HWE may be a non-hazardous traditional and complementary medicine in treating hyperglycemia and related problems, substantiating as an anti-hyperglycemic agent.